India - Maharashtra : Reorienting Government to Facilitate Growth and Reduce Poverty, Volume 2. Statistical Appendix, Other Annexes, and Workshop Programs - World Bank (Washington, DC, 2013)
Maharashtra's leadership position in India is under threat. The State is facing several bottlenecks to development: the private sector is no longer embracing Maharashtra and the public sector banks are increasingly reluctant to assist Maharashtra in its off-budget endeavors. Thus, the status quo is not an option. Regaining its leadership position is well within Maharashtra's reach. Among its many strengths are: the large pool of literate and skilled labor force, a well-developed financial system, a talented bureaucracy, and willingness to break with the ways of the past. If the State can successfully implement its reform agenda, it can quickly rebound and be back on the path of growth and prosperity. The lessons of the past decade suggest two guiding principles: First, the Government needs to articulate the message that its reforms are not to hurt, but to help the farmers. If reforms are to succeed, they have to be pro-farmer and pro-poor. Maharashtra's fiscal stress, be it due to power and irrigation subsidies or due to the losses in cotton and sugar interventions, has a close connection with the rural sector. However, as analyzed in Chapter 4, the current rural interventions are imposing a huge and unsustainable fiscal cost on the state, and more importantly, the bulk of the benefits are accruing to the rural rich. the challenge for the government, therefore, is to provide more efficient, equitable, and sustainable assistance to the rural poor. Second, the government's reform program needs to be designed and implemented with a medium- to long-term perspective. Piecemeal, short-term reforms can only bring short-term gains. The Government of Maharashtra faces a simple choice: to try to succeed in a difficult reform endeavor, or, since the policies of the past no longer work, to give up without trying and condemn itself to developmental and fiscal failure. Through its 2002-03 Budget Speech, the Government has indicated that it has chosen the former path. The quicker it moves along it, the greater the chances of success.